Phospholipase C-β1 and β4 Contribute to Non-Genetic Cell-to-Cell Variability in Histamine-Induced Calcium Signals in HeLa Cells - Ishida, Sachiko (Public Library of Science, 2014)
A uniform extracellular stimulus triggers cell-specific patterns of Ca(2+) signals, even in genetically identical cell populations. However, the underlying mechanism that generates the cell-to-cell variability remains unknown. We monitored cytosolic inositol 1,4,5-trisphosphate (IP(3)) concentration changes using a fluorescent IP(3) sensor in single HeLa cells showing different patterns of histamine-induced Ca(2+) oscillations in terms of the time constant of Ca(2+) spike amplitude decay and the Ca(2+) oscillation frequency. HeLa cells stimulated with histamine exhibited a considerable variation in the temporal pattern of Ca(2+) signals and we found that there were cell-specific IP(3) dynamics depending on the patterns of Ca(2+) signals. RT-PCR and western blot analyses showed that phospholipase C (PLC)-β1, -β3, -β4, -γ1, -δ3 and -ε were expressed at relatively high levels in HeLa cells. Small interfering RNA-mediated silencing of PLC isozymes revealed that PLC-β1 and PLC-β4 were specifically involved in the histamine-induced IP(3) increases in HeLa cells. Modulation of IP(3) dynamics by knockdown or overexpression of the isozymes PLC-β1 and PLC-β4 resulted in specific changes in the characteristics of Ca(2+) oscillations, such as the time constant of the temporal changes in the Ca(2+) spike amplitude and the Ca(2+) oscillation frequency, within the range of the cell-to-cell variability found in wild-type cell populations. These findings indicate that the heterogeneity in the process of IP(3) production, rather than IP(3)-induced Ca(2+) release, can cause cell-to-cell variability in the patterns of Ca(2+) signals and that PLC-β1 and PLC-β4 contribute to generate cell-specific Ca(2+) signals evoked by G protein-coupled receptor stimulation.